Makna Ekologis Ritual Tumpek Uduh dalam Perspektif Tri Hita Karana pada Masyarakat Bali - Paulus Kus Bukan; Edy Supriyanto; Yohanis Resubun (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2026)
This article aims to explore the richness of values, concepts, and paradigms embedded in Balinese local culture related to ecology. As a cohesive social community, the Balinese people possess indigenous wisdom that forms the foundation of an ecological philosophy: Tri Hita Karana. This principle serves as an ethical foundation inspiring the spirit of environmental stewardship for the sake of life’s harmony. Tri Hita Karana is concretely implemented through cultural rituals expressing reverence for nature, most notably Tumpek Uduh. Tumpek Uduh constitutes a ritual expression of gratitude toward nature, understood as a manifestation of the Divine. This study employs a qualitative methodology with a literature-based approach. Based on the findings of this study, the author concludes that Balinese society holds a profound reservoir of values for protecting and preserving the natural environment. Through the ritual of Tumpek Uduh, grounded in the philosophy of Tri Hita Karana, the Balinese offer a locally rooted ethical perspective for evaluating and understanding nature. Grounded in this rich philosophical heritage, the Balinese do not view nature merely as an material resource; rather, they perceive it as a manifestation of the Divine endowing nature with intrinsic spiritual significance and thus demanding respect, protection, and preservation.